Predictors of malignant lymph node involvement in patients with mediastinal lymphadenopathy and previous cancer: A cohort study. Issue 4 (14th January 2022) - Fiterman, Noy; Berkman, Neville; Kuint, Rottem
Abstract: Background: Mediastinal lymphadenopathy is a common finding in follow‐up after diagnosis of malignancy, and may represent recurrence of malignancy, or benign processes such as sarcoidosis. CT and PET‐CT are commonly used, despite limited ability to discriminate between benign and malignant disease, and although EBUS‐guided bronchoscopy is often performed, it is relatively invasive and may not always be safe in high‐risk patients. Clinical and radiological predictors for cancer recurrence could therefore be of value. Methods: A retrospective cohort analysis of all patients with mediastinal lymphadenopathy and previous malignancy undergoing mediastinal lymph node sampling via bronchoscopy was undertaken. Demographics, smoking status, details of previous malignancy, time since cancer diagnosis, and imaging data were collected, as well as follow‐up in the years following the procedure. We then compared specific characteristics of patients with malignant and benign lymphadenopathy in order to identify predictors of malignant versus benign lymphadenopathy. Results: A total of 113 patients were analyzed of which 63% had tumor recurrence, while the rest had benign disease including sarcoidosis. Smoking history and previous lung cancer were both correlated with lymph node malignancy, while symmetric hilar enlargement, and the presence of multiple pathological stations were correlated with benign outcome. Size, maximal SUV uptake or time interval since cancer diagnosis were not associated with the final diagnosis. Conclusions: These findings may help in assessing the pretest probability of tumor recurrence in patients with mediastinal lymphadenopathy, thus aiding in the clinical decision‐making in such scenarios. Abstract : Study aims and main results